Since you are dividing the two's both in the numerator and the denominator each of them cancel out and you are left with:
Hi, I'm having a slight bit of trouble grasping the concept of the general quadratic formula, the part that involves surds.
I have the question: Simplify 2+2 to the square root of 5 divided by 2.
I also have a few other things i may need assistance on, but i'll start here.
The quadratic formula says:
Given a quadratic of the form
ax^2 + bx + c = 0
then the roots are given by the formula
x = [-b +/- sqrt(b^2 - 4ac)]/2a
so you just plug in the numbers in their respective positions.
e.g. Solve 2x^2 + 5x + 1 = 0
=> x = [-5 +/- sqrt(25 - 4(2)(1)]/2*2 = [-5 +/- sqrt(17)]/4
so x = [-5 + sqrt(17)]/4 or x = [-5 - sqrt(17)]/4
Note: the roots of a function of x are the x values that cause the function to be zero. so once we have a quadratic = 0, solving for x gives the roots
Ahh, i think my meaning was misinterpreted.
I mean by 2+2 to the square root of 5 divided by 2 as everything past the divide is the numerator, and the 2 is the dinominator
qbkr21, how did you make that picture, i would be able to show you if i had that program